If the Body Politic Could Breathe in the Age of the Refugee An Embodied Philosophy of Interconnection - Metzger-Traber, Julia (Masters of Peace,, 2018)
This book posits that the 'refugee crisis' may actually be a crisis of identity in a rapidly changing world. It argues that Western conceptions of the individual 'Self' shape metaphors of political homes, and thus the geopolitics of belonging and exclusion. Metzger-Traber creatively re-conceives political belonging by perceiving the interconnection of each 'Self' through its most immediate home - the breathing body. On an experimental literary journey through her own past and that of Germany, she puts political philosophy in conversation with somatic and spiritual insight to expand notions of 'Self' and 'Home'. Then she asks: What ethical imperatives arise? What kinds of homes and homelands would we create if we no longer thought we ended at our skin? Contents The Borders of Belonging and the Question of Roots The Politics of Shaping Home An Emergent Ethic: Sensing Response-Ability A Practice of Paradox: Breathing Life into Theory Autopoiesis: Co-creating Home in Berlin Opening into the Abyss Target Groups Lecturers and students of psychology, especially in the field of peacebuilding, reconciliation and conflict transformation, political science, philosophy, social and cultural theory Actors in the fields of Elicitive Conflict Transformation, peace work, political science, political philosophy, expressive arts therapy The Author Julia Metzger-Traber is a peace researcher from the MA program in Peace, Development, Security and International Conflict Transformation at the University of Innsbruck, Austria. She is engaged in facilitating collaborative public art projects and community restorative justice processes as peace work.